Development of immunosensors for the detection of malaria. - Hemben, Aver (Cranfield University, 2017)
Malaria is a disease of global importance caused by an Apicomplexan Plasmodium parasite and transmitted by adult female Anopheles mosquitoes. Malaria affects approximately 50% of the world’s population causing millions of deaths every year. Mostly affected are pregnant women and children under 5 years of age. Morbidity and mortality rates are on the decline in some areas. Despite control efforts the disease continues to affect productivity. Productivity can be increased by early detection. Methods for malaria detection include blood film microscopy, immunochromatographic, serological and molecular tests. Blood film microscopy shows the highest sensitivity and specificity when used by trained personnel with reliable instruments. It is however time-consuming and cannot be applied as a point-of-care diagnostic method. Two electrochemical immunosensors for malaria biomarkers Plasmodium falciparum histidine rich protein 2 (PfHRP 2) and parasite L-Lactate dehydrogenase (LDH) were developed in this work for the detection and quantification of Plasmodium species. The methods were based on screen-printed gold electrodes (SPGEs) with on board carbon counter and silver /silver chloride (Ag / AgCl) pseudo-reference electrode. The first stage of the work involved comparison by characterization of the bare SPGEs using potassium ferricyanide. Electrochemical techniques were used to compare bare and self-assembled monolayers of mercaptoundecanoic acid (MUA) and 3,3´- dithiodipropionic acid (DTDPA) against bare SPGE. The optimal sensor was then used for antibody attachment. For the second stage of the work, adsorption was investigated for capture antibody immobilization on the SPGE. HuCAL monoclonal antibodies against PfHRP 2 conjugated to the electroactive enzyme horseradish peroxidase (HRP) were then applied for signal generation. Electrochemical measurements were conducted using 3,3´ 5,5´-tetramethylbenzidine dihydrochloride and hydrogen,peroxide (TMB / H₂O₂) as the mediator / substrate system at potential of -0.2 V. The sensors utilized sandwich enzyme-linked immunosorbent assay (ELISA),format with HuCAL monoclonal antibodies against Plasmodium immobilized on the gold working electrode. The developed biosensor was capable of detecting sub-microscopic Plasmodium infection with a linear range from 1 to 100 ng mL⁻¹ and a limit of detection (LOD) as low as 2.14 ng mL⁻¹ and 2.95 ng mL⁻¹ for PfHRP 2 in buffer and serum assays respectively. When compared with AuNP enhanced assays, the LOD was 36 pg mL⁻¹ and 40 pg mL⁻¹.. Another biomarker Plasmodium falciparum parasite Lactate dehydrogenase (LDH) was also investigated and another sensor developed using a sandwich assay similar to the PfHRP 2 sensor, but incorporating different antibodies against LDH. LOD 1.80 ng mL⁻¹ and 0.70 ng mL⁻¹ for LDH was obtained in buffer and serum assays. When compared with AuNP enhanced assays, the LOD was 19 pg mL⁻¹ and 23 pg mL⁻¹ respectively. As part of the work, culture medium supernatant containing PfHRP 2 and LDH was used to compare the immunosensor sensitivity for the pan-malaria antigen LDH. Sensitivity of the immunosensor was compared against commercially available Plasmodium immunochromatographic (ICT) kits: OptiMAL-IT and BinaxNOW Malaria kits. The optimized immuno-electrochemical biosensor detected the antigen at 0.002 % parasitaemia whereas the OptiMAL-IT ICT was only able to detect the LDH antigen when concentrations were of 2% parasitaemia. BinaxNOW ICT detected both the LDH and PfHRP 2 antigens in concentrations of 4% parasitaemia and showed negative reading at 0.5%parasitaemia in both synchronized and asynchronized samples. This study has developed two highly sensitive, portable and low cost malaria immunosensors for the first time on JD SPGEs. LDH immunosensor detects all Plasmodium species while PfHRP 2 immunosensor is specific for the detection of Plasmodium falciparum biomarker. Both immunosensors detect quantifiable, sub-microscopic levels of the biomarkers with sensitivities higher than the ICT tests. The immunosensors are therefore recommended for field trial.
Keywords: Malaria; antigen detection; immuno-electrochemical biosensor; diagnosis; PfHRP 2; LDH; immunosensor